Healthcare through Retail Medical Clinics: A Critical Analysis (Trinity Journal of Management, IT & Media (TJMITM), 2013)
The most true and sensible quote 'Health is Wealth' is  deliberated whenever there is a point of discussion on  healthcare. Healthcare is primary concern for every  human being and also for the stakeholders of health care  industry. Healthcare services now days are gauged with  Quality, Cost and Delivery parameters for evaluation. This  paper aims at providing the analytical view on the  healthcare services provided through Retail Medical  Clinics in Delhi. The landscape of retail medical clinics and  their contribution for affordable and accessible healthcare  to the people across the social and economic class has  been critically analyzed in the paper. This paper highlights  the innovative way of providing healthcare with strategies  adopted by the pharmacies, retail clinic owners for a  profitable business. It has been expected that this new  sector of retail medical clinics will emerge as a leading  healthcare provider, while growing its scope of services  with respect to location and better health plans for the  customers. The issue of healthcare services such as  inaccessible primary health care services, unnecessary  healthcare expenditure borne by the customer and  emergency requirement of healthcare fulfillment are  addressed in the paper and how the Retail Medical Clinics  will be beneficial is deliberated in the paper. The growth  and evolution of retail medical clinics highlight opportunities with innovative ways other than the  traditional way of delivery of health care services through  doctors at hospitals and with an improved value  proposition for the Indian health care system.
Keywords: Retail; Medical; Clinics; Healthcare; Innovation